May I steal your sentences? Brazilian modernists debate the issue of authorship - Machado, Marcia Regina Jaschke (Revista Criação & Crítica, 2014)
The topic of authorship has been thoroughly debated among Brazilian modernist intellectuals, especially during the 1920s. What we call search for the  authorial personality of modern styles was often linked to notions of influence and plagiarism. This article aims at presenting this debate in texts published at the time and in letters exchanged between Mário de Andrade and some of his interlocutors.